2019
DOI: 10.30831/akukeg.407029
|View full text |Cite
|
Sign up to set email alerts
|

E-öğrenme Ortamlarında Öğrenme Stilleri ve Akademik Başarı Arasındaki İlişkinin İncelenmesi

Abstract: In this study, the effects of students learning styles on academic achievement was investigated in elearning environments and the answer for the question "are e-learning style, participation in online course and watching the lecture videos offline predictors of academic achievement?" is tried to examined. E-Learning Style Scale (Gülbahar and Alper, 2014) and Achievement Test were applied 501 (350 female and 151 male) students who received pedagogical formation education in e-learning environment during the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
(24 reference statements)
3
2
0
3
Order By: Relevance
“…In other words, it can be stated that the increase in the perception of information technology self-efficacy will increase the motivation towards e-learning environments. This finding in the study points to results consistent with similar research findings (Ergün & Kurnaz, 2019;Yıldız & Seferoğlu, 2020). This result shows that doing activities and practices that will increase the information technology self-efficacy perceptions of gifted students will also positively affect their interest and motivation towards online learning environments.…”
Section: Discussionsupporting
confidence: 93%
“…In other words, it can be stated that the increase in the perception of information technology self-efficacy will increase the motivation towards e-learning environments. This finding in the study points to results consistent with similar research findings (Ergün & Kurnaz, 2019;Yıldız & Seferoğlu, 2020). This result shows that doing activities and practices that will increase the information technology self-efficacy perceptions of gifted students will also positively affect their interest and motivation towards online learning environments.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, we concluded that the students with the mentioned learning styles accepted and adapted to the online learning process more quickly and thought online learning to be more appealing and useful, considering their traits. While some studies documented that learning styles are likely to be influential in students' attitudes and achievement, supporting our finding (Bostrom, Olfman, & Sein, 1993;Ergün & Kurnaz, 2019;Lindsay, 1999), some others (Hajizainuddin, 1999;Desai, 1996) did not reach a significant relationship between learning styles and attitudes toward learning.…”
Section: Discussionsupporting
confidence: 80%
“…In his study analyzing the achievement of students having traditional education and distance education, Durak (2009) found that distance education students had higher achievement in both midterm and final exams rather than the students having traditional education. Kurnaz and Ergün (2019) stated in their study that there was a positive and low-level relationship between having a formal learning style and academic achievement, and active learning was also a predictor of academic achievement. In the literature, there were studies related to the positive effect of e-learning styles upon academic achievement (Hsu, 1994;Ross, Drysdale, & Schulz, 2001), as well as the findings related to absence of a relationship between learning styles and academic achievement (Omar et al, 2015;Rovai & Grooms, 2004).…”
Section: Discussionmentioning
confidence: 99%